A new species of Polylepis (Rosaceae) from the Bosque de Proteccion Pui-Pui, Peru - Valenzuela Gamarra, Luis; Valdivia, Maria Isabel Villalba (Phytotaxa, 2024)
A new species of Polylepis (Rosaceae) from the Humid Puna of the Bosque de Proteccion Pui-Pui in Junin, Peru, is described and illustrated. The new species was found at 3800 m elevation, in small patches or forest relicts of the natural protected area, growing in open areas highly exposed to wind and abundant fog, along with other shrubby species, mainly Chusquea tessellata (Poaceae). It is very similar to Polylepis canoi but differs by trifoliolate leaves with larger leaflets, lanuginose abaxially, and rounded to ovoid achenes, smaller than those of P. canoi. We also present details on its geographic distribution, ecological notes, and an assessment of the conservation status of the new species.